Impact of age on outcomes after transcatheter tricuspid valve edge-to-edge repair: insights from EuroTR - Novotny, Julia; Schlegel, Philipp; Konstandin, Mathias (Clinical research in cardiology, 2025)
Age stratified data regarding symptomatic and survival outcome of patients undergoing transcatheter tricuspid valve edge-to-edge repair (T-TEER) for severe tricuspid regurgitation (TR) are scarce. Aim of this study was to evaluate TR reduction, symptomatic outcomes, and survival following T-TEER stratified by patient age at intervention.
Gesehen am 20.01.2026